2018–2019 Florida Citrus Production Guide: Asian Citrus Psyllid and Citrus Leafminer - Philip A. Stansly; Jawwad A. Qureshi; Lukasz L. Stelinski; Michael E. Rogers (EDIS)
This 9-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by P. A. Stansly, J. A. Qureshi, L. L. Stelinski, and M. E. Rogers, and published by the Department of Entomology and Nematology, January 2019.